Influence of Organizational Factors, Social Factors, Individual Factors of Information Technology Acceptance on Perceived Usefulness at Bank Syariah Indonesia (BSI) Samarinda - Eko Adi Widyanto; Muhammad Suyudi; Angga Kusumah; Ruhmi Meysha Stinha (Bulletin of Community Engagement, 2024)
This study is to evaluate the impact of organizational, social, and individual factors on Information Technology acceptance and its effect on the perception of convenience at Bank Syariah Indonesia, Samarinda City. This research utilized primary data obtained via questionnaires. The study sample comprises personnel with access to T24 software at Bank Syariah Indonesia in Samarinda City. The purposive sampling method was employed for sample selection, resulting in a total of 62 research samples. The data analysis methodology was evaluated utilizing Statistical Product and Service Solutions (SPSS) Statistics version 26. The employed data analysis procedures included descriptive statistics, data quality assessments, assumption tests for classification, multiple linear regression analysis, t-tests, F-tests, and determination tests (R²/R Square). The findings of this study indicate that (1) Organizational Factors exert a positive and significant influence on perceived usefulness; (2) Social Factors exert a positive and significant influence on perceived usefulness; (3) Individual Factors exert a positive and significant influence on perceived usefulness; and (4) Organizational Factors, Social Factors, and Individual Factors collectively exert a positive and significant influence on perceived usefulness.